Hospital Preparedness for Outbreak at Patan Hospital: Lesson Learnt from COVID-19 - Shrestha, Ashis; Rajbhandari, Piyush; Bajracharya, Sumana (Journal of Nepal Health Research Council, 2020)
Patan Academy of Health Sciences started preparedness for COVID-19 in response to increasing number of patient in neighboring country. Outbreak preparedness in resource limited setup is challenging. Despite this, preparedness was done in reference to WHO interim guidance utilizing best available resources. During this preparedness, one patient was isolated as suspected COVID-19. This paper presents level of preparedness achieved with the limited resources and the lesson learned while isolating the patient.Keywords: COVID-19; Disaster; hospital preparedness